Effects of the global crisis on Macedonia: A counterfactual analysis - Rilind Kabashi (National Bank of the Republic of Macedonia, 2014)
This study investigates the effects of the global financial and economic crisis on Macedonia, with a particular focus on the period between 2008 and 2010. The counterfactual approach is used, according to which various hypothetical scenarios are created in order to simulate the movements of the main macroeconomic variables in absence of particular crisis transmission channels. In addition, the effects of monetary policy on macroeconomic variables during the crisis are also analysed. The empirical investigation utilises the Macedonian Policy Analysis Model, which is a small New Keynesian gap model of the National Bank of the Republic of Macedonia for forecasting and policy analysis. Main results indicate that the foreign demand and prices are the main factor for the fall of GDP and inflation and the slowdown in foreign trade. The loss of confidence and domestic financial factors also negatively affected the domestic economy, but their impact was relatively smaller. In the acute stage of the crisis, monetary policy was forced to react to pressures on foreign exchange market. However, there are indications that, once the situation in the foreign exchange market stabilised, monetary policy started to support economic growth.
Keywords: E37; E58; E65; 330; global crisis; counterfactual analysis; Macedonia